THE EFFECT OF TEACHER LEADERSHIP AND STUDENT MOTIVATION THROUGH COLLABORATIVE LEARNING ON STUDENTS' COGNITIVE ABILITIES AT XYZ PRIMARY SCHOOL - Victoria Tiauw; Yao Tung Khoe (JOHME: Journal of Holistic Mathematics Education, 2022)
During the COVID-19 pandemic, students were educated via online learning. Teachers and students around the world faced considerable challenges in coping with the sudden shifts in teaching and learning methods. In facing this challenge, teachers were required to be creative leaders in their teaching approach. Both teachers and students had to adapt quickly to change. One way to make learning more enjoyable and interesting is through collaborative learning. During online learning, teachers may use the Breakout Room feature of the Zoom application for collaborative learning. Teacher leadership and student motivation are two important elements in sustaining collaborative learning. The purpose of this quantitative study was to examine the effect of teacher leadership and student motivation through collaborative learning on the cognitive abilities of students at XYZ Elementary School. Thirty-six grade six students completed the online questionnaire. Research calculations using path analysis through the PLS SEM software were used to test the proposed hypothesis. The results showed that teacher leadership had a positive effect on collaborative learning and students' cognitive abilities. It was also found that student motivation had a positive effect on collaborative learning and students' cognitive abilities. Finally, collaborative learning has a positive impact on students’ cognitive abilities. BAHASA INDONESIA ABSTRACT: Dalam masa pandemi COVID-19, siswa harus melalui pendidikan mereka dengan pembelajaran daring dan pembelajaran jarak jauh. Guru dan siswa di seluruh dunia mengalami tantangan yang cukup berat untuk mengatasi perpindahan metode pembelajaran dan pengajaran yang mendadak. Dalam menghadapi tantangan ini, guru dituntut untuk menjadi pemimpin yang kreatif dalam mengajar dan para guru dan siswa harus cepat beradaptasi dengan perubahan. Salah satu cara untuk membuat pembelajaran menjadi lebih menyenangkan adalah melalui pembelajaran kolaboratif. Pembelajaran kolaboratif dalam pembelajaran daring dapat menggunakan fitur Breakout Room dari aplikasi Zoom. Kepemimpinan guru dan motivasi siswa adalah dua elemen penting dalam keberlangsungan dan keberhasilan pembelajaran kolaboratif. Tujuan dari penelitian kuantitatif ini adalah untuk menguji pengaruh kepemimpinan guru dan motivasi siswa melalui pembelajaran kolaboratif terhadap kemampuan kognitif siswa di Sekolah Dasar XYZ. Tiga puluh enam siswa SD Kelas 6 menyelesaikan kuesioner online. Perhitungan penelitian menggunakan analisis jalur melalui metode PLS SEM digunakan untuk menguji hipotesis yang diajukan. Hasil penelitian menunjukkan bahwa kepemimpinan guru berpengaruh positif terhadap pembelajaran kolaboratif dan kemampuan kognitif siswa. Ditemukan juga bahwa motivasi siswa berpengaruh positif terhadap pembelajaran kolaboratif dan kemampuan kognitif siswa. Hasil terakhir adalah pembelajaran kolaboratif berdampak positif terhadap kemampuan kognitif siswa